Pelatihan Digital Branding Dengan Media Sosial Melalui Pengelolaan Homestay di Desa Wisata Leuwimalang Bogor - Murhadi (Politeknik Sahid, 2025)
ABSTRACT The development of information technology and social media has changed branding patterns in tourism activities, including in homestay management in Leuwimalang Tourism Village. However, many homestay managers do not yet have the skills to optimally utilize digital media to build brand awareness or a positive image of the tourist village, which can increase the attractiveness of potential tourists. This community service activity aims to improve the digital branding communication capacity of homestay managers in Leuwimalang Tourism Village, Bogor through training in creating engaging, informative, and relevant social media content. The methods used included material delivery, interactive discussions on engaging and informative content concepts, and direct discussions on content creation by homestay managers. The training was attended by homestay managers who are residents of Leuwimalang Tourism Village. The results of this activity indicate that content published on the website and Instagram account needs to be updated with photos of activities that are current, informative, interesting, and consistent in terms of display. In addition, training participants gained an increased understanding of digital branding, photo and video production skills, and the ability to manage social media accounts and websites professionally. In conclusion, this training is effective in increasing the capacity of branding and promotional communication through digital media in homestay management, which is expected to have an impact on increasing tourist visits and the economic sustainability of tourist villages. Keywoards: digital branding, homestay, media sosial, desa wisata, pelatihan ABSTRAK Perkembangan teknologi informasi dan media sosial telah mengubah pola branding pada aktivitas pariwisata, termasuk dalam pengelolaan homestay di Desa Wisata Leuwimalang. Namun, banyak pengelola homestay yang belum memiliki keterampilan secara optimal dalam memanfaatkan media digital untuk membangun brand awareness atau citra positif desa wisata, yang dapat meningkatkan daya tarik calon wisatawan. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas komunikasi digital branding pengelola homestay di Desa Wisata Leuwimalang Bogor melalui pelatihan pembuatan konten media sosial yang menarik, informatif, dan relevan. Metode yang digunakan meliputi penyampaian materi, diskusi interaktif mengenai konsep konten yang menarik dan informatif, serta diskusi langsung dalam pembuatan konten oleh para pengelola homestay. Pelatihan diikuti oleh pengelola homestay yaitu warga Desa Wisata Leuwimalang. Hasil kegiatan ini menunjukkan bahwa konten yang dipublikasikan di website maupun akun Instagram perlu adanya pembaharuan dengan foto-foto kegiatan yang terkini, informatif, menarik, dan konsisten dari sisi penayangan. Selain itu, peserta pelatihan mendapat peningkatan pemahaman terkait digital branding, keterampilan produksi foto dan video, serta kemampuan mengelola akun media sosial dan website secara profesional. Kesimpulan, pelatihan ini efektif dalam meningkatkan kapasitas komunikasi branding dan promosi melalui media digital pada pengelolaan homestay, yang diharapkan akan berdampak pada peningkatan kunjungan wisatawan dan keberlanjutan ekonomi desa wisata. Kata Kunci: digital branding, homestay, social media, tourist village, training